The Motivation of Teachers at Beidun School, Heping County - Le, Cai; Wonglek, Pusit (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The objectives of this research were 1) to study the motivation of teachers at Beidun School, Heping County. And 2) to compare the motivation of teachers at Beidun School, Heping County by demographic factors such as gender, age, marital status, education level, work experience, and income. The population consisted of 116 teachers from Beidun School in Heping County. The instrument of this research was a questionnaire; it had valued the overall reliability of 0.98. The statistics which were used in the data analysis were percentage, mean ( and standard deviation (. The hypothesis testing used a mean comparison table. The research results found that: 1) The motivation of teachers at Beidun School, Heping County. Overall, it was at the high level. When considering each aspect, it was found that the motivation of teachers at high level with 2 aspects and at moderate level with 1 aspect. The highest level of growth needs, followed by relatedness needs, and existence needs, respectively. And 2) The teachers from Beidun School, Heping County, who were of different ages, and work experience had different levels of motivation overall. But the teachers from Beidun School, Heping County, who had different genders, marital statuses, and levels of education had no different levels of motivation overall and all aspects. The objectives of this research were 1) to study the motivation of teachers at Beidun School, Heping County. And 2) to compare the motivation of teachers at Beidun School, Heping County by demographic factors such as gender, age, marital status, education level, work experience, and income. The population consisted of 116 teachers from Beidun School in Heping County. The instrument of this research was a questionnaire; it had valued the overall reliability of 0.98. The statistics which were used in the data analysis were percentage, mean ( and standard deviation (. The hypothesis testing used a mean comparison table. The research results found that: 1) The motivation of teachers at Beidun School, Heping County. Overall, it was at the high level. When considering each aspect, it was found that the motivation of teachers at high level with 2 aspects and at moderate level with 1 aspect. The highest level of growth needs, followed by relatedness needs, and existence needs, respectively. And 2) The teachers from Beidun School, Heping County, who were of different ages, and work experience had different levels of motivation overall. But the teachers from Beidun School, Heping County, who had different genders, marital statuses, and levels of education had no different levels of motivation overall and all aspects.